Bionanocomposites reinforced with cellulose nanofibers derived from sugarcane bagasse. (13th June 2016) - Rani, Anuradha; Monga, Sheetal; Bansal, Monica; Sharma, Anupama
Abstract : Thermoplastic starch (TPS)/cellulose nanofiber (CNF) based nanocomposites were prepared by thermally plasticizing regular cornstarch by sorbitol and reinforcing it with cellulose nanofibers extracted from sugarcane bagasse using alkali steam explosion coupled with high shear homogenization. High shear results in shearing of the fiber agglomerates resulting in uniformly dispersed nanofibers. Final nanofibers size was found in the range of 30–40 nm. Various analytical techniques were used to characterize cellulose nanofibrils and thermoplastic starch/cellulose nanofiber based nanocomposites like scanning electron microscopy (SEM), X‐ray diffraction (XRD), and Fourier transform infrared (FTIR) spectroscopy. Tensile and barrier properties of prepared nanocomposites were also examined. Nano‐reinforcement resulted in substantial improvement of mechanical and barrier properties of the composites as compared to the neat polymer. POLYM. COMPOS., 39:E55–E64, 2018. © 2016 Society of Plastics Engineers